2013
DOI: 10.1007/s00540-013-1656-y
|View full text |Cite
|
Sign up to set email alerts
|

Lower incidence of emergence agitation in children after propofol anesthesia compared with sevoflurane: a meta-analysis of randomized controlled trials

Abstract: Our meta-analysis demonstrated that EA in children is less likely to occur after propofol anesthesia compared with sevoflurane anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
60
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 29 publications
4
60
0
3
Order By: Relevance
“…The results were confirmed in our analysis. It has also been demonstrated by Kanaya et al in their analysis that emergence agitation in children is less likely to occur after propofol anesthesia compared with sevoflurane anesthesia [60]. Similar results were also reported by Costi et al [61] There is also a meta-analysis revealing that emergence agitation occurred more frequently with sevoflurane than with halothane anesthesia in children [62].…”
Section: Discussionsupporting
confidence: 55%
“…The results were confirmed in our analysis. It has also been demonstrated by Kanaya et al in their analysis that emergence agitation in children is less likely to occur after propofol anesthesia compared with sevoflurane anesthesia [60]. Similar results were also reported by Costi et al [61] There is also a meta-analysis revealing that emergence agitation occurred more frequently with sevoflurane than with halothane anesthesia in children [62].…”
Section: Discussionsupporting
confidence: 55%
“…Sevoflurane is associated with a high incidence of EA, and there is a general agreement amongst anesthetists that sevoflurane can increase the incidence of EA in the recovery stage in children compared to propofol [3][5]. Meta-analysis confirmed that EA occurs more frequently in children under sevoflurane anesthesia than under propofol anesthesia [26]. In addition, another meta-analysis demonstrated that EA occurs more frequently under sevoflurane anesthesia than under halothane anesthesia [5].…”
Section: Discussionmentioning
confidence: 95%
“…The low blood–gas solubility and rapid recovery characteristics of sevoflurane may contribute to EA [29][34]. In a meta-analysis of Kanaya et al [26] showed that the incidence of EA is higher under sevoflurane anesthesia than that under propofol anesthesia in children, extubation time in propofol group was slightly longer (WMD = 1.09 min, 95% CI 0.096 to 2.09), however, because of the significant data heterogeneity, it is difficult to confirm whether rapid emergence plays a role in the higher incidence of EA after sevoflurane anesthesia. In our findings that children administered dexmedetomidine had slightly prolonged extubation time, and emergence time (WMD = 0.617 min, 95% CI 0.276 to 0.958, and WMD = 0.997 min, 95% CI 0.392 to 1.561 respectively), and lower incidence of EA.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies that have compared propofol infusions with sevoflurane, opioids have been added to the propofol arm, thus making interpretation difficult. However, a recent meta-analysis has shown a much lower incidence of emergence delirium with propofol compared with sevoflurane [27], and even if the anaesthetic was sevofluranebased, a single dose of 1 mg.kg…”
mentioning
confidence: 99%